Productivity and economics of Aonla - based hortipastoral system under semi-arid condition - Kumar, Sunil; Shukla, A.K. (Indian Journal of Agroforestry, 2020)
An experiment was conducted to utilize interspaces of grownup aonla plantation (10 years old) with different pasture species to optimize forage and fruit production. Associated pasture species did not show any negative impact on growth and yield of aonla. However, maximum fruit production (14.8t1ha) was recorded with intercropping with Caribbean stylo. The pasture production was 33.3 percent higher in association with tree as compared to sole pasture (3.0 t OM/ha). Among pasture combination guinea grass + Caribbean stylo produced significantly higher yield (5.1 t OM/ ha in association with tree 4.5 t OM/ ha as sole) as compared to sole Guinea grass and Caribbean stylo. Crude protein yield was significantly higher (450.7 kg/ha in association with tree and 427.9 kg/ha as sole) in mixed pasture combination (Guinea + S.hamata) as compared to pure Guinea grass or S.hamata. The maximum 8: C ratio was recorded when aonla trees were intercropped with Guinea + S.hamata (1 :6.29). The soil nutrient build up was also noticed in association with aonla tree.